ISOMORPHISM AND ALLOMORPHISM IN THE PHONETIC AND GRAPHEMIC PECULIARITIES OF CONSONANTS IN THE ENGLISH AND UZBEK LANGUAGES (Scientific journal of the Fergana State University, 2024)
The article is devoted to determining phonetically and graphemically isomorphic and allomorphic properties of consonant phonemes in the English and Uzbek languages. In the article, the distribution of consonants in both languages, the ways of how they are expressed in writing, as well as the specific peculiarities of consonants that do not have a mutual alternative in the compared languages, are revealed with specific examples. At the end of the article, it was concluded that the differences in the articulatory-acoustic properties of consonants, their unique occurrence in writing, means that the consonant system in the Uzbek and English languages ​​cannot be phonetically and graphemically equivalent.